Breeding Partners Have Dissimilar Foraging Strategies in a Long‐Lived Arctic Seabird - Marianne Gousy‐Leblanc; Allison Patterson; H. Grant Gilchrist; Vicki L. Friesen; Kyle H. Elliott (Ecology and Evolution)
ABSTRACT For long‐lived species with biparental care, coordination and compatibility in the foraging behavior of breeding mates may be crucial to successfully raise offspring. While high foraging success is clearly important to reproductive success, it might be equally important that the mate has a complementary foraging strategy. We test whether breeding partners have similar or dissimilar foraging strategies in a species where both partners share breeding responsibilities and exhibit high mate fidelity (thick‐billed murre; Uria lomvia). To examine whether thick‐billed murres showed complementary in foraging strategies, we attached GPS accelerometers to both partners within 40 thick‐billed murre chick‐rearing pairs. Individuals within a breeding pair were dissimilar in their foraging trip distance and in their number of dives during foraging trips compared to randomized pairs. Breeding partners were also more similar in wing length than randomized pairs. This result could be related to individual quality as individuals select similar sized partners or select sites that lead to similar sized partners. We conclude that foraging strategy diversity could be maintained in this population either because individuals prefer partners with foraging strategies complementary to their own, or because partners diverge in foraging strategies over multiple breeding season together.